RETROSPECTIVE ANALYSIS OF THE SCIENTIFIC POTENTIAL FORMATION OF DNIPROPETROVSK NATIONAL UNIVERSITY OF RAILWAY TRANSPORT NAMED AFTER ACADEMICIAN V. LAZARYAN - Myamlin, S. V.; Ahiienko, I. V. (Science and Transport Progress, 2015)
Purpose. The study involves the analysis of stages, formation forms and methods of the scientific potential of Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan (DNURT) and contribution of its staff in the development of national and world science. Methogology. The use of historical and chronological, comparative, descriptive methods of research, systematization and analysis of archival documents of domestic and foreign funds allows identifying formation forms and means of scientific potential of DNURT over the 85 years of its existence. The periodization method makes it possible to distinguish the main stages and peculiarities of this process. The methods of analysis and synthesis as well as methods of expert assessments were applied. Findings. On the basis of a detailed analysis of the considerable archival documents array the basic stages of scientific potential formation of DNURT in the 85 years of its existence were highlighted. Their features with taking into account the historical and social conditions as well as contribution of university faculty generations (and some individuals) in this process were determined. The forms and methods of continuity of scientific personnel and the impact of their research within the academic schools, formed at the Dnipropetrovsk Institute of Engineers of Railway Transport (DIERT) were analyzed. Up to the present they play a significant role in strengthening the authority of DNURT as a leading national institution of higher education and principal scientific organization in the field of railway transport and transport construction. Main stages of the University formation beginning from specialized industry institution to the Polytechnic Research University with modern scientific base for theoretical and experimental research were highlighted. Originality. In the research context concerning reforming problems of higher education system as one of the areas of generation and translation of scientific knowledge, the analysis of the scientific potential formation of one of the largest national Universities is important. It is connected with the fact that the genesis of the Western European system of higher education has some other constraints of time and space, and the most importantly – it has completely different structural unit – the classical University. For the first time on the basis of periodization the forms and methods formation of the scientific potential of Industry University were focused, their uniqueness from the point of view of the prevailing historical conditions was revealed, the forming process of scientific schools as an important component in the development of national science was analyzed. On the base of the analysis of archival documents it was proved that in all periods of University history, the important determinant of its scientific potential increase and high performance achievements is the relationship between the University and production, and in this particular case – with the problems and future of railway transport development. Practical value. The results of the paper can be used at creation of historiographical papers and study guides on issues of higher education; research of formation and development the issues of national scientific schools and traditions of the University of Ukrainian science, in the course of lectures on disciplines «History of railway transport development», «Introduction to specialty», and «Methodology of engineering activity».